MALNUTRITION IN THE SURGICAL PATIENTS - Andonovska, Biljana; Kuzmanovska, Biljana; Andonovski, Alan; Kartalov, Andrijan; Petrovska Cvetkovska, Dragana (SANAMED, 2016)
The term "malnutrition" is a broad term used to describe any imbalance in the diet. In 2009 it was confirmed that malnutrition is an urgent health problem. The reasons for which malnutrition may develop are different. Loss on cellular, physical and physiological level happens as a consequence of malnutrition. Studies show that in surgical practice there is malnutrition in 50% of patients and that there is a association between inadequate nutritional status and surgical result. It leads to prolonged treatment, increasing of the level of morbidity and mortality, increased hospital costs, etc. Sometimes malnutrition is unrecognised, untreated and worsened in hospitals. For this reason this paper will elaborate: nutrition and a surgical patient, assessment of a nutritional status, assessment of energy requirements, and enteral and parenteral nutrition in order to determine the conditions and procedures that affect the appearance, recognition and treatment of malnutrition.
Keywords: assessment of energy requirements; enteral nutrition; malnutrition; nutritional assessment; parenteral nutrition; surgical patient